Lyg1 deficiency aggravated LPS-induced chronic epididymal inflammation and sperm dysfunction in mouse - Liu, XueXia; Zhang, YuXiao; Wei, JiaLu; Gong, BenJiao; Wang, XiaoXin; Liu, FuJun (Frontiers in Immunology, 2025)
IntroductionChronic epididymitis threatens male fertility, yet the role of LYG1 in this disease is unclear. LYG1, an immunomodulatory protein, is highly expressed in the mouse epididymis, especially the cauda region prone to fibrosis. This study aimed to explore whether Lyg1 deficiency exacerbates LPS-induced epididymal inflammation, fibrosis and sperm dysfunction.MethodsSixty-four wild-type (WT) and Lyg1 knockout (KO) mice were divided into four groups. LPS was used to induce chronic epididymitis, with PBS as control. After 42 days, histological staining, flow cytometry, oxidative stress detection, transcriptomic profiling, sperm function analysis and In Vitro Fertilization (IVF) were performed to evaluate related indexes.ResultsUnder physiological conditions, Lyg1 KO mice had normal reproductive phenotypes. However, LPS-induced inflammation led to more severe epididymal damage, enhanced oxidative stress, abnormal ECM pathways and worse sperm dysfunction (reduced acrosomal integrity and functional proteins) in KO mice. IVF showed a more significant decrease in fertilization rate in KO mice.DiscussionLYG1 regulates the balance between epididymal inflammation and tissue repair. Its deficiency aggravates LPS-induced epididymal fibrosis and sperm dysfunction. This study identifies LYG1-dependent pathways as potential therapeutic targets for chronic epididymitis-related infertility.